The Female Dimension of the Board of Directors and its Impact on Firm Value: A Narrative Review - Giuseppe Granata; Anna Turchetta; Sara Gigli; Antonio Cennamo (European Scientific Journal, ESJ, 2025)
The aim of this paper is to investigate the relationship between the female presence on boards of directors and its impact on value creation. Creating value within companies is crucial because it ensures long-term sustainability, strengthens competitiveness, and enhances the ability to respond to crises and market changes. Boards of directors are the core decision-making bodies, where strategic choices are made that determine the future trajectory of organizations. In this sense, “value” must be understood as economic performance and the broader set of tangible and intangible benefits contributing to innovation, resilience, and stakeholder trust. We started from the following RQ: “How does female representation on boards of directors influence firm value?”. To answer this, we provided a critical and narrative review of the most significant academic research papers dedicated to studying the culture of women’s enterprises. The search was conducted using Scopus.  The study was conducted to offer a new key to reading these phenomena.Our findings indicate a significant increase in publications on this topic starting from 2019, peaking in 2023 with nine research papers. What emerges is that female representation on boards of directors has a positive impact, but it is not uniform. For instance, it strengthens firm value, but the intensity of benefits depends on the institutional, cultural, and sectoral context in which the company operates.